Circular Economy Based Food Waste Management in Public Feeding Programs: A Systematic Review of Makan Bergizi Gratis Implementation - Zahra Nabilla; Eliana Sari; Muhammad Zid; Achmad Husen; I Made Astra (Jurnal Green Growth dan Manajemen Lingkungan, 2025)
The Free Nutritious Meal (Makan Bergizi Gratis/MBG) program is an Indonesian government initiative aimed at improving nutrition for vulnerable populations, implemented through Nutrition Service Units (SPPG). However, its operations generate significant food, packaging, and wastewater, contributing to environmental impacts if not properly managed. This study conducts a Systematic Literature Review (SLR) of publications from 2018–2025 to examine circular economy-based waste management in institutional food services. Findings reveal that food waste is predominantly organic and driven by technical, behavioral, and institutional factors. Although circular economy principles such as reduce, reuse, recycle, and recover are widely discussed, their implementation remains fragmented and context-specific. A key gap exists between holistic circular economy concepts and partial real-world application, particularly in government-led food programs in developing countries. This study proposes an integrated conceptual framework combining technical, behavioral, and institutional dimensions to support sustainable waste management in SPPG and strengthen MBG program sustainability.